Analisis Biaya Operasional Alat Berat pada Pekerjaan Timbunan - Febrianti, Dian; Zakia, Zakia; Mawardi, Edi (University of Muhammadiyah Aceh, 2021)
Heavy equipment plays an important role in construction work, especially road construction work. The advantage of using heavy equipment is that it can get the job done faster. Improper use of heavy equipment will cause losses, so an analysis of operational costs is very necessary. Accurate and complete calculation of heavy equipment operational costs will help companies to make decisions, especially from a financial perspective. The purpose of this study was to determine the analysis of the operating costs of heavy equipment, and to know the proper and proper handling of heavy equipment. Cost analysis on heavy equipment is expected to provide benefits to be able to plan heavy equipment management in a coordinated, effective and sustainable manner. This research was conducted on the project Peningkatan Jalan Alun-Alun Suka Makmue-Jalan Lingkar Timur Ibu Kota Tahap II which is located in the district Nagan Raya. This study uses a qualitative method with a descriptive approach, namely research that seeks to describe problem solving based on data that will be obtained in the field. This research was conducted on four types of heavy equipment, namely excavators, motor graders, vibrator rollers and water tanker trucks. The results of the calculation of the operational cost analysis of excavator heavy equipment Rp. 738,617 per hour, motor grader Rp. 572,401 per hour, vibrator roller Rp. 499,735 per hour and water tanker truck Rp. 348,859 per hour. From the results obtained, it shows that for heavy equipment excavators and motor graders there has not been a return on capital, while for heavy equipment vibrator rollers and water tankers there has been a return on capital. So for heavy equipment, vibrator rollers and water tanker trucks, it is feasible to replace them with new tools